Digital Dimension of Cultural Capital: The (In)Visible Advantages for Students Who Exhibit Computer Skills. (April 2013) - Paino, Maria; Renzulli, Linda A.
We update theories of teacher expectancy and cultural capital by linking them to discussions of technology. We argue for broadening the span of culturally important forms of capital by including the digital dimension of cultural capital. Based on data from the third-grade and fifth-grade waves of the Early Childhood Longitudinal Survey–Kindergarten cohort (ECLS-K), results suggest a comprehensive model where teachers play a prominent, mediating role in the effects of computer proficiency on academic achievement. These findings have practical applications within classrooms, which can lead to a reduction in stratification. Our findings modernize and renew theoretical tools for understanding teacher and student interactions and the effects on achievement outcomes